Taḥqīq al-Farq bayna al-Sunan al-Ilāhiyyat wa al-Sunan al-Kauniyyat wa Ta’ṡīruhumā fī al-Tafsīr: Dirāsatun Muqāranatun bayna Tafsīr al-Manār wa Tafsīr al-Jawāhir [Investigating the Difference of Sunnah al-Ilāhiah and Sunnah al-Kauniah and Its Implication on Qur’anic Exegesis: A Comparative Study between Tafsīr al-Manār and Tafsīr al-Jawāhir] - Mukhamad Agus Zuhurul Fuqohak; Yuyun Affandi (UIN Sunan Kalijaga Yogyakarta, 2020)
This article aims at explaining the difference between sunan ilāhiyya ijtimāʿiyya and sunan kawniyya ṭabīʿiyya; two complicated concepts that are not easy to comprehend. Furthermore, as a means to help comprehension upon the concepts, this study also investigates their influences in Qurʾān commentaries. In doing so, this qualitative research employs analytical-comparative approaches upon Tafsīr al-Manār of Muḥammad Rashīd Riḍā and al-Jawāhir fī Tafsīr al-Qurʿān al-Karīm of Ṭanṭawī al-Jawharī. It is through both commentaries this article seeks to explain the difference between sunan ilāhiyya ijtimāʿiyya and sunan kawniyya ṭabīʿiyya. The result of the research is as follow: sunan ilāhiyya ṭabīʿiyya is a concept that is related to human and its intentionality and will, whereas sunan ṭabī’iyya is related to human but not in its intentionality but physicality. Sunan ijtimāʿiyya is reflected by Tafsīr al-Manār of Rashīd Riḍā, whereas sunan kawniyya ṭabīʿiyya is reflected by Tafsīr al-Jawāhir of Ṭanṭawī Jawharī. أوضح هذا البحث الفرق بين السنن الإلهية في المجتمع والسنن الكونية في الطبيعة وأثرهما في كتب التفسير. وقد استخدم هذا البحث الكيفي منهج التحليل والمقارنة بين تفسير المنار لمحمد رشيد رضا وكتاب الجواهر في تفسير القرآن الكريم لطنطاوي جوهري. ونتائج هذا البحث أن السنن الإلهية في المجتمع تتعلق بعزيمة وقدرة الإنسان. وأما السنن الكونية في الطبيعة لم تتعلق بالإنسان، لكن بالأحكام الطبيعية والعالمية. السنن الإلهية في المجتمع متضمنة في تفسير المنار لمحمد رشيد رضا، وأما السنن الكونية في الطبيعة متضمنة في كتاب الجواهر في تفسير القرآن الكريم لطنطاوي جوهري.